Hubungan Pengurusan Sistem Sekolah Kualiti dengan Produktiviti Guru (Sains Humanika, 2014)
This descriptive study aims to establish the relationship between Quality School Management System (SPSK) and quality and productivity of teachers. Fifty six school administrators including headmasters/headmistresses, senior assistants in charge of curriculum, students’ affairs and co-curricular activities from 14 pilot primary schools in Johor Bahru were involved. The researcher used data from 2011 SPSK Verification Summary Report to look at the level of SPSK practice and questionnaire by Rahmah (1977) was used as an instrument to gauge level of quality and productivity of teachers. SPSK practice showed a high level and the dominant aspects were Time-Table management, Teaching and Learning management, Checking of Pupils’ Work management, Examination management and Panel management while the dominant aspects of teacher quality and productivity level were personality, knowledge, skills and leadership. Correlation analysis proved there was a significant relationship between practice of SPSK and level of teacher quality and productivity. Recommendations for further actions by related authorities and future research were also presented.
Keywords: Quality management; teacher productivity